2020
DOI: 10.3390/metabo10090347
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of the Staphylococcal Volatilome Composition on Microbial Nutrition

Abstract: In vitro cultivation of staphylococci is fundamental to both clinical and research microbiology, but few studies, to-date, have investigated how the differences in rich media can influence the volatilome of cultivated bacteria. The objective of this study was to determine the influence of rich media composition on the chemical characteristics of the volatilomes of Staphylococcus aureus and Staphylococcus epidermidis. S. aureus (ATCC 12600) and S. epidermidis (ATCC 12228) were cultured in triplicate in four ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 84 publications
2
22
2
Order By: Relevance
“…Metformin was isolated utilising an adapted version of the liquid–liquid extraction previously described 69 . Briefly, the tissues were weighed (between ~ 2 to 20 mg) or biological fluids pipetted (~ 10 µL) into 2 mL screw cap Eppendorf plastic tube (Eppendorf, Stevenage, UK) along with a single 5 mm stainless steel ball bearing.…”
Section: Methodsmentioning
confidence: 99%
“…Metformin was isolated utilising an adapted version of the liquid–liquid extraction previously described 69 . Briefly, the tissues were weighed (between ~ 2 to 20 mg) or biological fluids pipetted (~ 10 µL) into 2 mL screw cap Eppendorf plastic tube (Eppendorf, Stevenage, UK) along with a single 5 mm stainless steel ball bearing.…”
Section: Methodsmentioning
confidence: 99%
“…Second, our data show that the growth phase of the organism has a strong influence on the volatilome, and therefore, using in vitro culture conditions that can most closely replicate the in vivo environment and microbial growth phases may increase the likelihood of putative biomarker translation from bench to bedside. In addition to controlling the growth phase of dimorphic organisms, macronutrient, micronutrient, and oxygen availability should all be considered in the development of in vitro model systems that replicate the in vivo physiology of the pathogen (14,17,(36)(37)(38)(39)(40)(41). In this study, we observed 35 VOCs present in at least 67% of all spherule strains (Fig.…”
Section: Downloaded Frommentioning
confidence: 58%
“…Since the emergence of antibiotic-resistant strains of S. aureus that caused epidemics in the 1950s and 1960s there have been large global efforts to develop early detection systems ( Cookson, 2011 ). In the last 15 years, the understanding of the core and accessory components of the S. aureus volatilome has been steadily growing due to a growing number of in vitro volatilomic profiling studies ( Bunge et al, 2008 ; Filipiak et al, 2012b ; Baptista et al, 2019 ; Fitzgerald et al, 2020 ; Jenkins and Bean, 2020 ). The clinical value of in vitro volatilomic profiling has been demonstrated by Filipiak et al (2015) who reported detection of VOCs, known to be emitted by S. aureus , in the breath of patients with S. aureus -positive respiratory infections.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity and mechanisms behind microbial volatilomes have been recently illustrated in several comprehensive review papers ( Schulz and Dickschat, 2007 ; Elmassry and Piechulla, 2020 ; Kai, 2020 ; Weisskopf et al, 2021 ) and books ( Ryu et al, 2020 ). Growth parameters such as growth media ( Jenkins and Bean, 2019 , 2020 ), growth phase ( Filipiak et al, 2012b ; Chen et al, 2016 ), oxygen content ( Insam and Seewald, 2010 ), temperature ( Misztal et al, 2018 ) and pH ( Schulz-Bohm et al, 2017 ), all influence microbial volatilomes. Another less studied factor in the overall variation seen across the volatilomes of microbial species is the occurrence of strain-level specificity in volatilomic emission within a given species ( Schulz et al, 2020 ; Weisskopf et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%